The potential of e-books to improve college students’ self-directed learning in biology - Fitri Olvia Rahmi; Evi Suryawati; Imam Mahadi (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Independence in learning is very necessary for the application of online learning. Students as learners must have Self Directed Learning. This study aims to develop independent learning resources to facilitate student learning independence. Development research using the ADDIE model is carried out until the development stage. Needs analysis is conducted on 49 Biology Education Students with data collection instruments using the SDL test consisting of 5 question indicators: 1) Identifying learning needs; 2) Set up study routines and discover concept mappings; 3) Using concept/outline mapping as a useful understanding various information; 4) Self-assessment, honing potential; 5) Can explore self-ability. The test results show that in indicator 1 there are 9 students (18.37%) and indicator 5 as many as 11 students (22.45%) who have SDL abilities. The results of the needs analysis become the basis for the development of interactive electronic books through features such as material summaries, images, animations, videos, references (links and barcodes), interactive exercises, keywords, interest facts, practice questions, formative tests, and reflections. It is hoped that this interactive e-book can increase the independence of undergraduate and PPG students in studying biotechnology material as a source of independent learning.Abstrak Kemandirian belajar sangat diperlukan dalam penerapan pembelajaran daring. Mahasiswa sebagai pembelajar harus memiliki kemandirian belajar (Self Directed Learning/SDL). Penelitian ini bertujuan untuk mengembangkan sumber belajar mandiri untuk memfasilitasi kemandirian belajar mahasiswa. Penelitian pengembangan menggunakan model ADDIE penelitian ini dilakukan sampai tahap development. Analisis kebutuhan, dilakukan pada 49 orang Mahasiswa Pendidikan Biologi dengan instrumen pengumpulan data menggunakan tes SDL terdiri dari 5 indikator pertanyaan: 1) Mengidentifikasi kebutuhan belajar; 2) Mengatur rutinitas belajar dan menemukan pemetaan konsep; 3) Menggunakan pemetaan konsep/garis besar sebagai metode yang berguna untuk memahami berbagai informasi; 4) Menilai sendiri, merefleksikan dan mengasah potensi; 5) Bisa mengeksplor kemampuan diri. Hasil tes menunjukkan pada indikator 1 sebanyak 9 orang (18,37%) dan 5 sebanyak 11 orang (22,45%) yang memiliki kemampuan SDL. Hasil analisis kebutuhan menjadi dasar untuk pengembangan buku elektronik interaktif melalui fitur-fitur barupa ringkasan materi, gambar, animasi, video, referensi (link dan barcode), latihan interaktif, key word, interesring fact, latihan soal, tes formatif dan refleksi. Diharapkan e-book interaktif ini dapat meningkatkan kemandirian mahasiswa S1 dan PPG dalam mempelajari materi bioteknologi sebagai sumber belajar mandiri.